Fatty Acid Profiling of Bali and Wagyu Cattle using Principal Component Analysis - Dairoh, Dairoh; Sutikno, Sutikno; Ishak, Andi Baso Lompengeng; Priyanto, Rudy; Sumantri, Cece; Ulum, Mokhamad Fakhrul; Jakaria, Jakaria (Buletin Peternakan, 2024)
This study aimed to compare the fatty acid profiles of Bali cattle and Wagyu cattle. A total of 50 beef was used in this study, consisting of 44 Bali cattle from Kupang, NTT, and 6 samples of Wagyu cattle from supermarkets. The fatty acid profiles identified are saturated and unsaturated (MUFA and PUFA). The fatty acid analysis used is the Gas Chromatography (GC) method. Descriptive analysis was used to examine data on the fatty acid profile, and T-test analyzed fatty acid composition differences between Bali and Wagyu beef. Differences in fatty acid compositions have been reported based on breeds. The Bali beef had significantly (p<0.05) higher saturated fatty acid than Wagyu. Several fatty acids of meat from Bali cattle were significantly different (p<0.05) from Wagyu, except for myristoleic (C14:0) and palmitoleic acids (C16:0) did not show significant differences (p>0.05). The principal component analysis (PCA) results showed that the first principal component was UFA, MUFA: SFA ratio, oleic acid, omega-9, MUFA, and palmitic acid. In contrast, the second principal component was myristoleic acid, linolenic acid, omega-3, PUFA: SFA ratio, PUFA, omega-6, linoleic acid, stearic acid, SFA, and palmitoleic acid. The study's findings revealed that Bali beef had a much more saturated fatty acid composition of Bali beef was higher than Wagyu beef. This result suggests that Wagyu cattle have a more favorable fatty acid profile, which benefits health.